KEBERADAAN BAKTERI PENGHASIL FITASE UNTUK PERBAIKAN KESUBURAN TANAH VERTISOL PADA BERBAGAI SISTEM BUDIDAYA TANAM DI KECAMATAN GONDANGREJO KABUPATEN KARANGANYAR - Santosa, Slamet; Sajidan, Sajidan (Prodi Pendidikan Biologi FKIP UNS, 2013)
This experiment aimed to investigate whether phytase-producing bacteria isolated from vertisol soil in Gondangrejo have bacterial diversity and the ability to fertilize the soil. This research is exploratif and laboratory experiments. Bacteria in the rice roots (PJ2, PJ3, PP2, PP8, PU2, and PU +1) has the ability to grow at 70°C, and its enzyme activity is stable at 80°C and pH 4-8. Bacteria in the corn roots still grow (JP1, JW1, JPJ1, JPS1) and still active at 60°C, and the enzyme still active at 60°C and pH 4-8. Bacteria on the beans roots grew well (KPTU4, KPJW1, KPTU3, KTJ2) and still active at 60°C, and the enzyme activity at 60°C and pH 4-7. Bacteria on the sugar cane roots grew well (TS1, TS2, TU1, TJ4), active at 60°C and the enzyme activity at 60°C and pH 4-8. Bacteria on the cassava roots were good (SW2) and still active grow at 60°C, and at 90°C and pH 4-8, the enzyme still active. Bacteria on the great pumpkin roots were good (WP1, WP3), still active at 60°C, and the active enzyme activity at 60°C and pH 5-8. Bacteria on the ?gambas? roots grow well (GPP2, OU1, OU2) and still active at 60°C, and the enzyme still active at 60°C and pH 4-8. Rough of extracted enzyme from isolates of the best area of rice roots PU+2 and PU+1, beans KTJ2 and KPJW, sugar cane TU1 and TU2, corn JP1 and JPJ1, ?gambas? GPP2 and OU2, were stable at 80°C. Selected isolates actived at pH 6-8 are PJ3, OU 2, WP1, WP4, JW1, JP1, KPtU 2, KJP1, KPtU4, TJ2, while PJ2 and TU1 were active in pH 6-9.Penelitian ini bertujuan untuk mengetahui apakah bakteri-bakteri yang diisolasi dari tanah vertisol daerah Kecamatan Gondangrejo mempunyai keragaman bakteri dan kemampuan untuk menghasilkan fitase. Penelitian ini bersifat ekploratif, pengumpulan data dari eksperimen laboratorium. Bakteri perakaran padi (PJ2, PJ3, PP2, PP8, PU2, dan PU+1) memiliki kemampuan tumbuh pada suhu 70°C, dan aktivitas enzimnya masih aktif suhu 80°C serta pH 4 ? 8. Bakteri perakaran jagung (JP1, JW1, JPJ1, JPS1) pertumbuhannya masih aktif suhu 60°C, dan aktivitas enzimnya aktif suhu 60°C serta pH 4 ? 8. Perakaran kacang (KPTU4, KPJW1, KPTU3, KTJ2) pertumbuhannya masih aktif suhu 60°C, dan aktivitas enzimnya aktif suhu 60°C serta pH 4 ? 7. Perakaran tebu (TS1, TS2, TU1, TJ4) pertumbuhannya masih aktif suhu 60°C dan aktivitas enzimnya aktif suhu 60°C serta pH 4 ? 8. Perakaran singkong (SW2) pertumbuhannya masih aktif suhu 60°C, dan aktivitas enzimnya aktif pada suhu 90°C serta pH 4 ? 8. Perakaran waluh (WP1, WP3) pertumbuhannya masih aktif suhu 60°C, dan aktivitas enzimnya aktif suhu 60°C serta pH 5 ? 8. Perakaran gambas (GPP2, OU1,OU2) pertumbuhannya masih aktif pada suhu 60°C, dan aktivitas enzimnya aktif suhu 60°C serta pH 4 ? 8. Ekstrak enzim kasar dari isolat terpilih untuk daerah perakaran padi yang paling bagus PU+2 dan PU+1, perakaran kacang KTJ2 dan KPJW1, perakaran tebu TU1 dan TU2, perakaran jagung JP1 dan JPJ1, perakaran gambas GPP2 dan OU2 keseluruhan ekstrak enzim stabil sampai suhu 80oC. Isolat terpilih aktif pada kondisi pH 6-8 PJ3, OU 2, WP1, WP4, JW1, JP1, KPtU2, KJP1, KPtU4, TJ2, sedangkan pH 6-9 PJ2 dan TU1.